Risks and challenges of the digital age for the sustainability of democratic values in political philosophy (Journal of Philosophy Culture and Political Science, 2026)
The relevance of the research stems from the growing need to reassess the sustainability of democratic values in the context of rapid digital transformation of the socio-political environment. The increasing influence of digital platforms, algorithmic systems, and mediatized communication channels has led to a shift in the traditional meanings of freedom, subjectivity, and publicity, requiring a philosophical reflection on their redefinition in new digital conditions. The aim of the study is to theoretically substantiate the resilience of democratic values in the digitally mediated environment and to define guidelines for their protection in the face of algorithmic governance, informational intermediation, and the restructuring of public space. The methodological framework combines comparative-historical and hermeneutic approaches with an interdisciplinary integration of political philosophy, media theory, and digital ethics. The study revealed that freedom is increasingly shaped as algorithmically managed choice, subjectivity as a construct of digital identities, and publicity as a dynamic, filtered flow of communication. It was established that mechanisms of democratic participation in the digital age are determined not only by civic will but also by the technical architecture of platforms and algorithmic logic. Identified threats include the erosion of individual autonomy, increased political polarization, declining trust in institutions, and unequal access to digital participation tools. The scientific novelty lies in the integrative analysis of both philosophical and infrastructural aspects of digital democracy, resulting in normative recommendations aimed at preserving core democratic values. Future research perspectives involve the development of ethical and legal models of digital self-governance, comparative analysis of platform regulation practices, and refinement of key concepts in political philosophy under the conditions of digital interaction.Keywords: digital subjectivity, algorithmic mediation, platform architecture, information filtering, political communication, digital rights, normative frameworks, public interaction.